2014
DOI: 10.1016/j.pedneo.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Parental Smoking During Pregnancy and Its Association with Low Birth Weight, Small for Gestational Age, and Preterm Birth Offspring: A Birth Cohort Study

Abstract: Maternal smoking is responsible for increased incidences of LBW and preterm delivery of babies, and therefore, smoking cessation/reduction should be advised to pregnant women to reduce morbidities in their neonates. Further studies are needed to clarify the correlation of fetal health with passive smoking, including exposure to environmental tobacco smoke and to other smokers in the family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
173
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(200 citation statements)
references
References 15 publications
17
173
3
7
Order By: Relevance
“…Although their prevalence was low, some maternal lifestyle factors, including smoking and alcohol consump tion, are likely to be underreported in the Birth Noti fications data set, relative to previous survey data. 43 There is also potential for residual confounding because of incomplete consideration of some essen tial nutritional elements associated with congenital heart disease, including folic acid and multivitamin supplementation, 8,9 These potential confounders were not available from the data source for this study. We used ICD9CM codes, which are not as specific as the ICD10CM codes; 18 this may have led to some misclassification of disease in both mothers and infants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although their prevalence was low, some maternal lifestyle factors, including smoking and alcohol consump tion, are likely to be underreported in the Birth Noti fications data set, relative to previous survey data. 43 There is also potential for residual confounding because of incomplete consideration of some essen tial nutritional elements associated with congenital heart disease, including folic acid and multivitamin supplementation, 8,9 These potential confounders were not available from the data source for this study. We used ICD9CM codes, which are not as specific as the ICD10CM codes; 18 this may have led to some misclassification of disease in both mothers and infants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Cigarette smoke contains mutagenic and carcinogenic agents, 3 as well as toxic agents, which can lead to fetal alterations [23][24][25] such as in the reproductive function stages (folliculogenesis, steroidogenesis, embryo transport, …”
Section: Discussionmentioning
confidence: 99%
“…Using Taiwan Birth Cohort to explore the effects of maternal smoking on birth outcomes, Ko et al [7] found that maternal smoking is associated with preterm delivery. The incidences of preterm birth of mothers who smoked during the different pregnancy stages increased with the number of cigarettes smoked daily, which was especially significant among those who smoked more than 20 cigarettes/day.…”
Section: Preterm Birthmentioning
confidence: 99%